2016
DOI: 10.1136/vr.103577
|View full text |Cite
|
Sign up to set email alerts
|

Pestivirus in alpine wild ruminants and sympatric livestock from the Cantabrian Mountains, Spain

Abstract: Bovine viral diarrhoea virus (BVDV) and Border disease virus (BDV) were investigated at the wildlife-livestock interface in the distribution area of chamois in the Cantabrian Mountains, North-Western Spain. From 2010 to 2014, sera from sympatric wild (n=167) and domestic (n=272) ruminants were analysed for pestivirus antibodies by cELISA, virus neutralisation test (VNT) and for the presence of pestiviral RNA using a reverse transcription (RT)-PCR. Results showed a higher seroprevalence in cattle (59.4 per cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
4
11
1
Order By: Relevance
“…conjunctivae [22]. Similar correspondences between the epidemiological scenarios in sympatric sheep and chamois have been also reported for other pathogens in the study area [50,51], highlighting the significance of spillover events among competent hosts at the wildlife-livestock interface, even if its occurrence is rare [52,53]. Even though independent sylvatic cycles accounted for most of the IKC cases in wild hosts from the Pyrenees, the higher prevalence and diversity of M .…”
Section: Discussionsupporting
confidence: 70%
“…conjunctivae [22]. Similar correspondences between the epidemiological scenarios in sympatric sheep and chamois have been also reported for other pathogens in the study area [50,51], highlighting the significance of spillover events among competent hosts at the wildlife-livestock interface, even if its occurrence is rare [52,53]. Even though independent sylvatic cycles accounted for most of the IKC cases in wild hosts from the Pyrenees, the higher prevalence and diversity of M .…”
Section: Discussionsupporting
confidence: 70%
“…It found only 1 of 892 red deer to be seropositive and concluded that the deer were spillover hosts only and did not represent a risk for domestic ruminants. Another study of sympatric alpine populations of livestock and wild ruminants, including deer in north‐west Spain generated similar findings (Fernández‐Aguilar et al., ).…”
Section: Assessmentsupporting
confidence: 58%
“…There is conflicting evidence in the literature surrounding prevalence of Pestivirus in cervids and known contact with cattle. Studies [18][19][20] have reported that close contact with cattle can induce high seroprevalence in wild cervids; however, a study by Frolich et al [21] contrasted these findings and hypothesized an independent cycle as responsible for intrapopulation persistence. Additionally, the identification of persistently infected mule deer (Odocoileus hemionus) [22] and white-tailed deer (Odocoileus virginianus) [23][24][25] suggests that BVDV can sustain itself in deer populations without contact with cattle.…”
Section: Discussionmentioning
confidence: 99%